The Effect of Work Discipline, Work Motivation and Work Commitment on Employees Performance - Helty, H.; Serang, Serlin; Amir, Muh. (Golden Ratio of Human Resource Management, 2023)
This research is quantitative research with an explanatory approach. The target population in this research were sales force employees at Toyota Hadji Kalla, Urip Sumoharjo Branch, Makassar City with a total sample of 42 employees. The sampling method in this research uses the census method. The data used in this research are primary and secondary data with data collection techniques in the form of observation, questionnaires, documentation and literature study. The analysis technique is validity and reliability testing, classical assumption testing and hypothesis testing using the multiple linear regression method.The research results show that Motivation and Commitment each have a positive and significant effect on employee performance, while Discipline has no effect on the performance of sales force employees at Toyota Hadji Kalla, Urip Sumoharjo Branch, Makassar City.